Poetyka zamieszkiwania - Konończuk, Elżbieta (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The author of the article attempts at defining the “poetics of dwelling” understood as a form of practicing a place, which a human is responsible for. Dwelling, the main problem of geopoetics according to the author, is analysed including the following discourses: literary, geographical, and architectural.